The Association Between Hepatitis B Virus Infection and Nonliver Malignancies in Persons Living with HIV: Results from the EuroSIDA Study - Mocroft, A (2021)
Objectives: The aim of this study was to assess the impact of hepatitis B virus (HBV) infection on non-liver malignancies in people living with HIV (PLWH). Methods: All persons aged ≥ 18 years with known hepatitis B virus (HBV) surface antigen (HBsAg) status after the latest of 1 January 2001 and enrolment in the EuroSIDA cohort (baseline) were included in the study; persons were categorized as HBV positive or negative using the latest HBsAg test and followed to their first diagnosis of nonliver malignancy or their last visit. Results: Of 17 485 PLWH included in the study, 1269 (7.2%) were HBV positive at baseline. During 151 766 person-years of follow-up (PYFU), there were 1298 nonliver malignancies, 1199 in those currently HBV negative [incidence rate (IR) 8.42/1000 PYFU; 95% confidence interval (CI) 7.94-8.90/1000 PYFU] and 99 in those HBV positive (IR 10.54/1000 PYFU; 95% CI 8.47-12.62/1000 PYFU). After adjustment for baseline confounders, there was a significantly increased incidence of nonliver malignancies in HBV-positive versus HBV-negative individuals [adjusted incidence rate ratio (aIRR) 1.23; 95% CI 1.00-1.51]. Compared to HBV-negative individuals, HBsAg-positive/HBV-DNA-positive individuals had significantly increased incidences of nonliver malignancies (aIRR 1.37; 95% CI 1.00-1.89) and NHL (aIRR 2.57; 95% CI 1.16-5.68). There was no significant association between HBV and lung or anal cancer. Conclusions: We found increased rates of nonliver malignancies in HBsAg-positive participants, the increases being most pronounced in those who were HBV DNA positive and for NHL. If confirmed, these results may have implications for increased cancer screening in HIV-positive subjects with chronic HBV infection.